2014
DOI: 10.1080/02614367.2014.962582
|View full text |Cite
|
Sign up to set email alerts
|

Clustering attendees at the Philharmonic Orchestra’s Summer Festival

Abstract: There has been an increase in the number of arts and music festivals held annually in South Africa. These festivals range from wide all-encompassing arts festivals, such as the National Arts Festival, to specific festivals that cater for very specific audiences, such as the Jazz Festival and the Philharmonic Orchestra Festival. It may therefore be expected that the attendees of the various types of festivals would differ quite substantially. While much research has been conducted to understand visitor behaviou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 27 publications
0
26
0
Order By: Relevance
“…The consumption of different musical categories is influenced by sociodemographic factors and motivations and the fact that different musical genres have different target audiences [13]. Music festivals have the potential to create benefits beyond the festival itself or the host destination, in particular by encouraging the appreciation of a musical genre, increasing the purchase of musical products, and promoting musical tourism, according to Kruger and Saayman [9,12].…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The consumption of different musical categories is influenced by sociodemographic factors and motivations and the fact that different musical genres have different target audiences [13]. Music festivals have the potential to create benefits beyond the festival itself or the host destination, in particular by encouraging the appreciation of a musical genre, increasing the purchase of musical products, and promoting musical tourism, according to Kruger and Saayman [9,12].…”
Section: Literature Reviewmentioning
confidence: 99%
“…To this end, the author identifies different variables that can be used in the segmentation process. According to Saayman and Saayman [13], market segmentation is important because visitors have different needs, motives, or lifestyles.…”
Section: Mason and Paggiaromentioning
confidence: 99%
See 1 more Smart Citation
“…Many authors have studied music festivals, among them [5], [6], [3], [7], [8], [9], [10] and [11]. [12] highlighted that the consumption of different musical categories is influenced by sociodemographic factors and motivations and that different musical genres have different target audiences. [11] concluded that music festivals have the potential to create benefits beyond the festival itself or the host destination, in particular by encouraging the appreciation of a musical genre, increasing the purchase of musical products, and promoting musical tourism.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They found that the most important motivator was enjoying the festival program and the celebratory atmosphere followed by learning the local culture and socialization. Saayman and Saayman (2016) investigated attendance for the South Africa Philharmonic Orchestra festival. Their questionnaire included demographics, attendance preference and motivation for attendance.…”
Section: Introductionmentioning
confidence: 99%